Analisis Faktor-Faktor yang Mempengaruhi Penggunaan Alat Kontrasepsi dan Fertilitas yang Ada di Kecamatan Denpasar Utara - I Putu Yoga Surya Pratama; Amrita Nugraheni Saraswaty (Gemawisata: Jurnal Ilmiah Pariwisata, 2024)
Based on data from the Central Statistics Agency (BPS) for 2021, the number of couples of childbearing age (PUS) in Denpasar City ranks third with a total of 81,575. In Denpasar City, the number of active family planning (FP) participants is 63,024, while those not using contraception number 10,730, and new FP participants amount to 7,840. Choosing contraception is not an easy task for healthcare providers or related agencies, as the decision must align with the individual needs of each person. In North Denpasar, there are 21,545 PUS, with 15,854 active FP participants and 5,691 not using contraception. The relatively low number of active FP participants in Denpasar City indicates a lack of understanding of the importance of contraception within families. The main issue in Denpasar City regarding the family planning program is the insufficient use of contraceptives, as evidenced by many families having more than two children, some even reaching five. This study aims to analyse the factors affecting contraceptive use in North Denpasar. Data analysis was performed using path analysis with SPSS software. The results indicate that: 1) education level negatively affects contraceptive use in North Denpasar; 2) income level and patriarchal culture positively affect contraceptive use in North Denpasar. This implies that higher income and stronger patriarchal culture are associated with higher contraceptive use in North Denpasar; 3) education level and income negatively but not significantly affect fertility in North Denpasar, suggesting that these factors do not have a significant impact on fertility; 4) patriarchal culture and contraceptive use positively but not significantly affect fertility in North Denpasar, indicating that these factors also do not significantly impact fertility.